REINFORCING STUDENTS’ READING ACHIEVEMENT BY USING READERS THEATER - Irna Irna; Muhammad Zuhri Dj; Uswatun Hasanah (Institut Agama Islam Negeri (IAIN) Bone, 2022)
This research was aimed at reinforcing student’s reading achievement by using the Readers Theater at the eleventh grade of SMAN 13 Bone. The research used the classroom action research with consisted of two cycles. The research was carried during six weeks at beginning on July 14th – August 18th 2020. The subject of this research was one class of the eleventh grades of SMAN 13 Bone. The data analyzes of the research were qualitative and quantitative. The research findings showed in the qualitative data, the students were motivated, confident and felt entertaining in learning reading. On other hand, in the quantitative data, the students mean score improved. The mean score in both Cycle I and Cycle II were 74.75 and 82.38. Therefore, the rate percentage based on the indicator achievement in both Cycle I and Cycle II running to enhance where the result was 37.6% to 78.2%. Both the qualitative and quantitative findings of this research showed there were reinforcing the students’ reading achievement by using the Readers Theater in classroom action research.